A Bibliometric Analysis of the Relationship Between Leadership Styles and Teacher Satisfaction in Education Management Research - Mislan Sihite; Asri Widiatsih; Loso Judijanto; Noor Fazariah Handayani (The Eastasouth Journal of Learning and Educations, 2023)
This research employs bibliometric analysis and keyword occurrence assessment to explore the intricate relationship between leadership style and teacher satisfaction within the realm of educational management research. The analysis encompasses influential documents, thematic clusters, and prevalent keywords, providing a comprehensive overview of the current state of the literature. Noteworthy findings include the identification of top-cited documents, the delineation of thematic clusters addressing diverse aspects of educational management, and a focus on keywords such as "Knowledge Management" and "Supply Chain Management." The results offer insights into the interdisciplinary nature of educational management, emphasizing the need for a holistic understanding of leadership dynamics and their impact on teacher satisfaction. The implications of these findings extend to educational practice, policy development, and future research directions, guiding stakeholders in optimizing leadership strategies for enhanced teacher well-being.